Study Of The Need For Academic Guidance And Counseling Services For Jambi Educational Administration Students - Yusra, Affan; Rasimin; Freddi Sarman (Universitas PGRI Yogyakarta, 2025)
Effective academic guidance and counseling services are crucial for student success, yet they often fail to address specific needs. In Indonesia’s higher education context, particularly at Jambi University, understanding these needs is essential for developing more responsive support systems. This study explores the academic guidance and counseling needs of Education Administration students at Jambi University, focusing on individual, organizational, academic, and social support aspects. Using a qualitative approach with purposive sampling, semi-structured interviews were conducted with 12 students from different cohorts. Findings indicate that individual and organizational needs such as emotional support, guidance in navigating the campus administration system, and social adaptation—are more prominent than academic and social needs. By identifying key student challenges, this study provides insights for designing localized academic guidance services. The findings contribute to improving counseling models in Indonesian higher education, ensuring they are more effective and aligned with students' actual needs. Keywords: study of needs, academic guidance and counseling services